2008
DOI: 10.1007/s11739-008-0153-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of end-tidal carbon dioxide role in predicting elevated SOFA scores and lactic acidosis

Abstract: The development of organ dysfunction is a key contributor to morbidity and mortality in sepsis. End-tidal carbon dioxide levels measured by non-invasive end-tidal capnography (ETCO2) may provide a rapid assessment of a patient's underlying metabolic status. The objective of this study was to explore the association between ETCO2 and (1) organ dysfunction [sequential organ failure assessment (SOFA) score], and (2) serum lactate levels in febrile emergency department (ED) patients. Prospective, observational coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…On the other hand, in another study 29 that found a moderate correlation between EtCO 2 and HCO 3 (r=0.506), it was obtained values of EtCO 2 ≤ 25, with a specificity of 84% for acidosis in its sample, and EtCO 2 ≥37mmHg, with 100% sensitivity for absence of metabolic acidosis. Still, in another previous study 30 , a weak inverse correlation was obtained between EtCO 2 and SOFA (r= -0.35, p<0.01) and between EtCO 2 and lactate (r= -0.35, p<0.01) in febrile and potentially septic patients. However, in a later study 18 , a moderate inverse correlation was found between EtCO 2 and lactate, according to the septic status: in patients with sepsis (r= -0.421, p<0.001), severe sepsis (r= -0.597, p<0.001), and septic shock (r= -0.482, p<0.011).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…On the other hand, in another study 29 that found a moderate correlation between EtCO 2 and HCO 3 (r=0.506), it was obtained values of EtCO 2 ≤ 25, with a specificity of 84% for acidosis in its sample, and EtCO 2 ≥37mmHg, with 100% sensitivity for absence of metabolic acidosis. Still, in another previous study 30 , a weak inverse correlation was obtained between EtCO 2 and SOFA (r= -0.35, p<0.01) and between EtCO 2 and lactate (r= -0.35, p<0.01) in febrile and potentially septic patients. However, in a later study 18 , a moderate inverse correlation was found between EtCO 2 and lactate, according to the septic status: in patients with sepsis (r= -0.421, p<0.001), severe sepsis (r= -0.597, p<0.001), and septic shock (r= -0.482, p<0.011).…”
Section: Resultsmentioning
confidence: 67%
“…Palma de Mallorca, IB, Spain, 2016AuthornCannula usedType of sensor Capnograph usedMeasurement durationPishbin et al ( 1 ) 64Nc*SidestreamCapnocheck (r) Sleep Capnograp/oximeter.NK/NA † Agus et al ( 11 ) 72Nc*MicrostreamMDE Escort Prism (r) monitorNK/NA † Gilhotra & Porter ( 23 ) 58Nc*SidestreamPhilips M3046A.1 minSolana et al ( 12 ) 25Nco ‡ MicrostreamPhilips smarth capnoline O2 pediatrics.30 sec-1minNagler et al ( 24 ) 130Nco ‡ MicrostreamMicrocap; Oridion.1-2 minKartal et al ( 29 ) 240O § SidestreamMedlab Cap 10 sidestream.NK/NA † McGillicuddy et al ( 30 ) 97NK/NA † MicrostreamNelcor NBP-70.NK/NA † Soleimanpour et al ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a need for new, simple, reliable and clinically available measurements to contribute to the definition of the sepsis. ETCO 2 levels, a good example of this, have been shown as a reliable measurement to identifying sepsis (38,39) and an accurate predictor of mortality. It was found that an ETCO 2 concentration less than 25 mmHg are strongly associated with serum lactate levels >4 mmol L -1 (38).…”
Section: Roadmap For the Futurementioning
confidence: 99%
“…
McGillicuddy et al [1] should be commended on their attempt to identify a non-invasive method of screening febrile patients for possible sepsis. It is now well accepted that sepsis is a life-threatening disease that needs to be identified as soon as possible; multiple studies have demonstrated that early, aggressive resuscitation leads to better outcomes [2,3].
…”
mentioning
confidence: 99%